2019
DOI: 10.3390/s19051184
|View full text |Cite
|
Sign up to set email alerts
|

A Fog Computing Solution for Context-Based Privacy Leakage Detection for Android Healthcare Devices

Abstract: Intelligent medical service system integrates wireless internet of things (WIoT), including medical sensors, wireless communications, and middleware techniques, so as to collect and analyze patients’ data to examine their physical conditions by many personal health devices (PHDs) in real time. However, large amount of malicious codes on the Android system can compromise consumers’ privacy, and further threat the hospital management or even the patients’ health. Furthermore, this sensor-rich system keeps genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…RFID protocol framework based on fog computing and blockchain is used for medical big data collection and data privacy protection [19][20][21]. Gu et al [19] proposed a security and privacy protection solution for fog computing, which designs a framework for security and privacy protection using fog computing and a privacy leakage based on contextbased dynamic and static information to improve health and medicine infrastructure. Silva et al [20] proposed a medical records management architecture based on fog computing.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…RFID protocol framework based on fog computing and blockchain is used for medical big data collection and data privacy protection [19][20][21]. Gu et al [19] proposed a security and privacy protection solution for fog computing, which designs a framework for security and privacy protection using fog computing and a privacy leakage based on contextbased dynamic and static information to improve health and medicine infrastructure. Silva et al [20] proposed a medical records management architecture based on fog computing.…”
Section: Related Workmentioning
confidence: 99%
“…Step 4 (17) Based on the received HMAC, WISP can confirm the timeliness of the message and the equality of the session keys calculated on both sides (18) After verifying successfully, Nbr++, K2 � � K' ⊕ NW; (19) WISP records (K2, Seq1, Nbr) to awaken the IMD antenna (20) When IMD detects the request, collects (K1, Seq1), and employs them to exchange data securely with the programmer. contrary, if the private key is used to encrypt data, only the corresponding public key can be used for decryption.…”
Section: Physiological Signals Data Sharing Model Based Onmentioning
confidence: 99%
“…We found that the leakage and loss of personal information was the main reason that prevented people from participating both in the two groups. We think this result may be due to the severe information leakage, which has been a common phenomenon in the internet age [35]. Apart from this, impairment of medical right and bias of exam results were also their concerns in our research.…”
Section: Discussionmentioning
confidence: 69%
“…The real-time feedback class encompasses solutions that aim at providing quick responses to critical situations in healthcare environments. Several articles target the most variate set of applications in that scope: (i) critical event detection [61,88]; (ii) warning systems [89]; (iii) security issues [49,90]; and (iv) breath support systems [91]; In the first topic, in [88], the authors implemented a real-time signal processing algorithm for fall detection, which is able to deliver information to caregivers. These algorithms are executed at the network's border by fog servers, which collect and process all health information.…”
Section: Real-time Feedbackmentioning
confidence: 99%